Advances in Shoulder Surgery - Sonar, Satish B. (IntechOpen, 2018)
The goal of this book is to provide readers with an update on recent developments in surgical treatment of some shoulder disorders. The perspective of this book involves highlighting management of complex shoulder conditions in better ways. This book is divided into four main sections: 'Repair' involves chapters related to primary repair; 'Replacement' section provides detailed perspective on shoulder replacement procedures for different conditions; 'Reconstruction' includes a chapter on reconstructive procedures where primary repair is not possible; and lastly 'Rehab and Miscellaneous' section includes chapters on surgical management of rheumatoid arthritis and rehab. Individual chapters provide a base for a wide range of readers including students, professors, physiotherapists and orthopaedic surgeons, who will find in this book simply explained basics as well as advanced techniques of shoulder surgeries. The book consists of ten chapeters, compiled by experts from institutes across the globe.